Influence of Chloride and Nitrate Anions on Copper Electrodeposition onto Au(111) from Deep Eutectic Solvents. Issue 19 (16th September 2022) - Geng, Tanja; Schick, Benjamin W.; Uhl, Matthias; Kuehne, Alexander J. C.; Kibler, Ludwig A.; Ceblin, Maximilian U.; Jacob, Timo
Abstract: Invited for this issue's Front Cover is the group of Prof. Timo Jacob in collaboration with Prof. Alexander Kuehne, both from Ulm University (Germany). The cover picture shows copper electrodeposition on a gold‐coated quartz crystal from copper(II) chloride in a choline chloride/ethylene glycol deep eutectic solvent (DES), as monitored by electrochemical quartz crystal microbalance (EQCM). Read the full text of the Research Article at 10.1002/celc.202101263 . Abstract : "Deep eutectic solvents (DESs) are mixtures of a salt with a hydrogen bond donor, which can be employed as electrolytes with beneficial properties for metal electrodeposition. Various copper(I) or copper(II) salts were added to binary mixtures of choline chloride or nitrate and ethylene glycol to study their effect on copper electrodeposition on Au(111). While Cu + is strongly stabilized by chloride, the deposition also proceeds from Cu + with a high concentration of nitrate anions being present…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Research Article at 10.1002/celc.202101263 .